P-glycoprotein and/or Histone Deacetylase 2 Regulates Steroid Responsiveness in Childhood Nephrotic Syndrome - Harshit Singh; Narayan Prasad; Durga Prasanna Misra; Akhilesh Kumar Jaiswal; Vikas Agarwal (Indian Journal of Rheumatology)
Background: P-glycoprotein (P-gp) overexpression in peripheral blood mononuclear cells (PBMCs) has been reported in patients with steroid-resistant nephrotic syndrome (SRNS). Glucocorticoids suppress NFκB-associated coactivator activity by deacetylation of histone by enzyme histone deacetylase (HDAC)-2. Interaction between HDAC2 activity and P-gp expression in childhood NS patients is not clear. Aim: This study aims to evaluate the role of HDAC2 and P-gp expression on PBMCs and steroid responsiveness in patients with childhood NS. Materials and Methods: Thirty-one patients were recruited at baseline (n = 31) (before initiating steroid therapy); after 6 weeks of steroid therapy, 24 patients achieved remission (steroid-sensitive NS [SSNS] n = 24 mean age, 7.96 ± 3.90), whereas seven patients were resistant to steroids (SRNS, n = 7, mean age 10.00 ± 3.55). mRNA expression of HDAC2 and P-gp and functional analysis of P-gp and enzymatic activity of HDAC2 were analyzed at baseline, and at 6 weeks of steroid treatment and at the time of relapse. Results: The expression of P-gp mRNA was significantly lower in individuals (n = 24) who achieved remission at 6-week steroid therapy as compared to baseline and those who were resistant (n = 7) to steroids (P < 0.005). Similarly, the expression of HDAC2 mRNA was significantly higher at baseline and at remission following 6-week steroid therapy as compared to their expression in those who were resistant to steroids (P < 0.005). The function of P-gp was significantly lower in NS patients who achieved remission after 6-week steroid therapy compared to baseline (P < 0.005), whereas it was not significant in resistant patients (P = 0.37). The enzymatic activity of HDAC2 was significantly higher in SSNS patients as compared SRNS patients at 6-week steroid therapy (P < 0.005). Conclusion: The expression and function of P-gp and HDAC2 may affect steroid response in NS patients. Combined therapy of steroids with P-gp inhibitor and/or HDAC2 inducers may have a rationale in management of SRNS patients.